Recommendations on sun exposure and photoprotection following easing of the COVID-19 pandemic lockdown: Spanish photobiology group of the spanish academy of dermatology and venerology (aedv) (2020)
We find ourselves in a socially atypical situation owing to the sudden change in our once normal living patterns. Our relationship with the environment has been affected by the COVID-19 pandemic, especially in terms of spending time outdoors. Lockdown has created a situation in which most people have had less exposure to sunlight than usual, and this in turn has led to a springtime where degrees of exposure are similar to, or even lower than,those of winter.In terms of exposure, therefore, we might say that we have had a longer winter. This in turn leads us to believe that as the positive effects of naturally progressive exposure to sunlight on the skin have diminished, the natural biological response in the skin has also been altered. Hence, cutaneous synthesis of vitamin░D, which is our greatest source of vitamin░D, has been hamperedby the lockdown, during which many people have not been exposed to sunlight in several weeks. Blood vitamin░D levels vary according to the season, with lower values in winter than in summer1; however, during the COVID-19 lockdown, the winter low-exposure period has been extended by more than 3░months. Low vitamin░D levels have pathophysiological consequences, and given that vitamin░D can reduce the risk of infection through various mechanisms, the possibility that a deficiency could render us more susceptible to infection by coronavirus is somewhat alarming.2 Consequently, various sectors, including health care, have recommended direct—albeit brief—exposure to sunlight in order to increase serum vitamin░Dlevels.3 Similarly, we should not forget the benefits of exposure to sunlight for our state of mind, which is considerably affected by the current situation, through stimulation of the neurotransmitters involved in the mechanisms underlying emotional well-being.